Moderating Influence of Curriculum, Pedagogy, and Assessment Practices on Learning Outcomes in Indonesian Secondary Education - Umami, Ida (Journal of Social Studies Education Research, 2018)
The purpose of this research was to examine the current situation and problems faced by Indonesian schools in curriculum, pedagogy, and assessment practices despite government’s several legal initiatives. A questionnaire comprising both open and closed-ended questions was sent to the teachers and public education officers of the Indonesian education department. Out of a total of 200 questionnaires distributed in three secondary schools of Papua and Bandung and the headquarters of Indonesian Education Department at Jakarta, only 170 respondents retuned the questionnaire. For the purpose of quantitative analysis, percentage, mean and standard deviation were calculated while content analysis method was utilized for qualitative data. The questions dealt with curriculum, pedagogy and assessment and their combined role in the achievement of learning outcomes of secondary education in Indonesia. Evidence collected from teacher’s questionnaire show that most participants held a good knowledge of curriculum, pedagogy and assessment practices gained through long experience in the education sector. The implications of this study have wide perspectives as its findings would be beneficial for policy making. Recommendations of the study focus on the implementation of good practices.